2012
DOI: 10.1002/rem.21318
|View full text |Cite
|
Sign up to set email alerts
|

Threshold amounts of organic carbon needed to initiate reductive dechlorination in groundwater systems

Abstract: Aquifer sediment and groundwater chemistry data from 15 Department of Defense facilities located throughout the United States were collected and analyzed with the goal of estimating the amount of natural organic carbon needed to initiate reductive dechlorination in groundwater systems.Aquifer sediments were analyzed for hydroxylamine and NaOH-extractable organic carbon, yielding a probable underestimate of potentially bioavailable organic carbon (PBOC). Aquifer sediments were also analyzed for total organic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…By varying the assumed fraction of bioavailable POC, it was found that the closest match to observed DO concentrations (Figure ) was obtained by assigning a fraction of bioavailable POC to be 0.15. That value is consistent with previous studies on POC bioavailability (Chapelle et al ; Thomas et al ).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…By varying the assumed fraction of bioavailable POC, it was found that the closest match to observed DO concentrations (Figure ) was obtained by assigning a fraction of bioavailable POC to be 0.15. That value is consistent with previous studies on POC bioavailability (Chapelle et al ; Thomas et al ).…”
Section: Resultssupporting
confidence: 94%
“…Previous studies have clearly demonstrated the importance of naturally occurring organic carbon driving the reductive dechlorination and natural attenuation of CEs in groundwater systems (U.S. EPA ; Bradley ; Chapelle et al ). However, it has not previously been feasible to couple the oxidation of naturally occurring DOC and POC coupled to CE reduction in order to model the vulnerability of public supply wells to contamination (Focazio et al ; Frind et al ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the 2015 field investigation, 21 soil borings were advanced to approximately 35 feet (10.7 m) bgs with a sonic drill at locations adjacent to each of the upgradient, biowall, and downgradient groundwater monitoring wells at seven of the eight transects sampled for groundwater; soil borings were not advanced at transect BE‐09 due to conflicts with existing utilities. Potentially bioavailable organic carbon (PBOC) from each of the 21 soil borings was analyzed at the laboratory of Dr. Mark Widdowson at the Virginia Polytechnic Institute and State University (Virginia Tech) by the PBOC methodology documented in Rectanus et al (), Chapelle et al (), Thomas et al (), and Lebrón et al (2013).…”
Section: Methodsmentioning
confidence: 99%